The specifics of the problem of working poverty in the context of food security - Khussainova, Zh.; Yeskendir, N.; Penev, N.; Nencheva, I. (BIO Web of Conferences, 2024)
The article is devoted to the study of the relationship between issues of food security and the problem of poverty, in particular, the poverty of the working population. The main features of poverty in Kazakhstan are identified and the factors that form the poverty of the working-age population are considered. Based on the analysis of the sectoral structure of employment, conclusions are drawn about the increased risk of spreading working poverty among the population of the Republic of Kazakhstan due to unemployment, reduced working hours, low labor productivity, the influx of labor resources in industries with low added value and low wages. The importance of creating favorable conditions for sustainable economic development and reducing income inequality among the working population is emphasized. Understanding the link between poverty and food insecurity will contribute to the development and implementation of a systemic social policy that ensures fair wages, as well as a socially equitable distribution of resources in society.